(3TQM QSGdI GdTjN YHOGddg Hf YKeGf aj JMbjb cdGe GdHjVGhis - (3GdTjN YHO Gddg Hf YKeGfs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI hGdSdGe ef Yjhf GddWGFa s
(3BNQgG (B:s
(3gPG BNQ eG ecffG Gddg ef JjSjQg hJfejJg ai JMQjQg s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs